Seismic Vulnerability Assessment of Steel Moment Resisting Frames with Consideration of Mainshock Aftershock Seismic Sequence - Torfehnejad, Mohammadmehdi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
This study assessment of the collapse capacity and mechanism of special steel moment frames (SSMFs) with considering earthquake shock sequences for structures height from 4 to 20 stories. The collapse capacity is expressed in terms of the Sa(T1) value at which the system reaches the collapse state. Collapse identification relies on the capability of the model to accurately simulate damage of members and the resulting behavior deterioration. The softening in the lateral response expressed in terms of maximum interstory drift (MID) when it is expressed against the Sa(T1) values is thus used to identify collapse occurrence. The mainshock-aftershock (MS-AS) effect and the uncertainties associated with it are simulated by utilizing a set of 32 natural record pairs. The level of damage induced by MS is represented by two parameters including MID and peak residual story drift (PRSD). Using these parameters, the MS is applied so as to various pre-selected damage levels are imposed. For each MS damage level, an incremental dynamic analysis (IDA) is performed using the AS record that follows MS and a free vibration phase. The AS intensity causing the collapse state is finally identified and respected for evaluating the effect of MS damage level. The correlation between the median collapse Sa’s, called aftershock median collapse capacity, and the MS damage indicated by MID and PRSD parameters is quantified. The collapse mechanism under the AS is also investigated by studying the distribution of maximum ductility demand (MDD) and contribution of members in the total hysteretic energy absorption, called energy absorption contribution (EAC). This investigation revealed that the EAC parameter provides better metrics for studying the collapse mechanism which is remarkably affected by the MS-AS sequence. Accordingly, the role of elements experiencing damage under the MS becomes less prominent in absorbing the AS energy and is substituted by contribution of elements with less deterioration under the MS. The members’ EAC is also shown to be affected by the percentage of the energy imposed by each individual shock as a fraction of the total energy imposed by the MS-AS sequence.

ÖZ: Bu çalışma, 4 ile 20 kat arası yüksekliğe sahip özel çelik moment çerçeveli (ÖÇMÇ'li) yapılar için ardarda oluşan deprem dizileri dikkate alınarak göçme kapasitesinin ve mekanizmasının değerlendirilmesini içermektedir. Göçme kapasitesi, sistemin göçme durumuna ulaştığı Sa(T1) değeri cinsinden ifade edilir. Göçme tanımlaması, oluşturulan modelin her bir elemanının hasar düzeyleri ve bunun sonucunda yapının davranışında oluşan çiddi değişimi doğru bir şekilde simüle etme yeteneğine dayanır. Sa(T1) değerlerine karşı gelen maksimum katlar arası ötelenme (MKÖ) cinsinden ifade edilen yanal tepkideki yumuşama ve aşırı öteleme çökme oluşumunu tanımlamak için kullanılır. Ana şok-artçı şok (AŞ-ARŞ) etkisi ve bununla ilişkili belirsizlikler, 32 doğal kayıt çifti kullanılarak simüle edilmiştir. MS tarafından indüklenen hasar seviyesi, MKÖ ve tepe kalıcı kat ötelenmesi (TKKÖ) dahil olmak üzere iki parametre ile temsil edilir. Bu parametreleri kullanarak, önceden seçilmiş çeşitli hasar seviyelerine ulaşacak şekilde AŞ uygulanır. Her AŞ hasar seviyesi için, AŞ'yi takip eden ARŞ kaydı ve bir serbest titreşim fazı kullanılarak artımsal dinamik analiz (ADA) gerçekleştirilir. Çökme durumuna neden olan ARŞ büyüklüğü nihayet tanımlanır ve AŞ hasar seviyesinin etkisini değerlendirmek için dikkate alınır. Artçı şok medyan çökme kapasitesi olarak adlandırılan medyan göçme Sa (T)'ları ile MKÖ ve TKKÖ parametreleri tarafından belirtilen AŞ hasarı arasındaki korelasyon nicelleştirilir. ARŞ kapsamındaki göçme mekanizması, maksimum süneklik talebinin (MST) dağılımı ve yapı elemanlarının toplam histeretik enerji absorpsiyonuna, enerji absorpsiyon katkısı (EAK) olarak adlandırılan katkısı incelenerek araştırılır. Bu araştırma, EAK parametresinin, AŞ-ARŞ dizisinden önemli ölçüde etkilenen çökme mekanizmasını incelemek için daha iyi ölçümler sağladığını ortaya koydu. Buna göre, AŞ altında hasar gören elemanların rolü, ARŞ enerjisini emmede daha az belirgin hale gelir ve AŞ altında daha az hasar gören elemanların katkısı ile değiştirilir. Yapı elemanlarının EAK'sinin, AŞ-ARŞ dizisi tarafından uygulanan toplam enerjinin bir bölümü olarak her bir deprem tarafından uygulanan enerjinin yüzdesinden de etkilendiği gösterilmiştir.
Doctor of Philosophy in Civil Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2022. Supervisor: Prof. Dr. Serhan Şensoy.
Keywords: Thesis Tez; Civil Engineering Department; Seismic Design; Buildings - Earthquake effects--Earthquake resistant design; Seismic collapse; mainshock-aftershock sequence; incremental dynamic analysis; median collapse capacity; steel moment frames; energy absorption distribution; inelastic demand distribution